2020
DOI: 10.36706/jtk.v26i1.439
|View full text |Cite
|
Sign up to set email alerts
|

Pemurnian minyak jelantah dengan menggunakan adsorben serbuk biji kelor tanpa karbonisasi dan bentonit

Abstract: Konsumsi minyak goreng masyarakat Indonesia hingga 2017 mencapai 2,36 juta ton. Angka tersebut menunjukkan ketersediaan minyak jelantah yang sangat besar. Minyak jelantah yang telah melalui proses adsorpsi dapat bernilai ekonomis, salah satunya menjadi bahan baku untuk industri biodiesel. Adsorben yang digunakan adalah serbuk biji kelor tanpa karbonisasi (BK) dan bentonit (B). Bentonit dikombinasikan dengan serbuk biji kelor sebagai pembanding dan untuk mencari kombinasi rasio yang tepat diantara keduanya. Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
0
9
1
4
Order By: Relevance
“…Based on SNI, the standard of free fatty acids in oil is 3.0 mg KOH/g and all treatments are considered to have met the quality requirements of SNI. When compared with Ayu and Diharmi (2019) the acid value obtained in this study was higher, whereas [17], study showed an acid value of 0.37 0.01 mg KOH/g showed lower free fatty acids than in this study. This is possible due to two factors, including the hydrolysis and storage prosesses.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Based on SNI, the standard of free fatty acids in oil is 3.0 mg KOH/g and all treatments are considered to have met the quality requirements of SNI. When compared with Ayu and Diharmi (2019) the acid value obtained in this study was higher, whereas [17], study showed an acid value of 0.37 0.01 mg KOH/g showed lower free fatty acids than in this study. This is possible due to two factors, including the hydrolysis and storage prosesses.…”
Section: Resultscontrasting
confidence: 80%
“…Research conducted by [16], showed that the addition of bentonite can reduce the free acid number of catfish oil from 1.72 after the addition of 2% bentonite to 1.150.23 and the peroxide number from 5.18 to 0. Other studies conducted by [17], show that the addition of activated carbon to tilapia fish oil has a relatively small peroxide value of 1.220.005% and an acid value of 3.120.23%. This shows that bentonite and activated carbon can reduce fat oxidation products, namely peroxides, aldehydes, and ketones.…”
Section: Resultsmentioning
confidence: 88%
“…The use of bagasse as an absorbent which is able to bind impurities in used cooking oil is like other types of absorbents used in oil refining such as bleaching earth and bleaching carbon. (Ramdja et al 2010). The use of bagasse in the refining of used cooking oil produced a chemical quality in the form of a significant decrease in the value of free fatty acids, the peroxide value and moisture content that were in accordance with the quality standards of cooking oil chemically were 0.3 of the maximum free fatty acid content, 1 for the maximum peroxide value, 0.3 for the maximum moisture content (Sulung et al 2019).…”
Section: Purification Of Used Cooking Oil With Adsorbentmentioning
confidence: 84%
“…The residue from the sugarcane juice mill was washed thoroughly and then dried in the blazing sun. Furthermore, the dried bagasse was ground by grinding and sifting to obtain bagasse powder (Ramdja et al 2010).…”
Section: Raw Materials Preparatiaon a Bagasse Processingmentioning
confidence: 99%
“…Beberapa penelitian tentang pengolahan minyak jelantah menggunakan metode adsorpsi sebagai metode yang paling sederhana untuk menurunkan bilangan asam dan bilangan peroksida. Beberapa peneliti sebelumnya juga telah melakukan penelitian tentang pengolahan minyak jelantah menggunakan adsorben dari bahan alam dengan memanfaatkan hasil samping atau limbah pertanian, seperti ampas tebu (Ramdja et al, 2010), arang aktif dari sabut kelapa (Yustinah & Hartini, 2011), karbon aktif dari biji kelor (Dahlan et al, 2013), ampas pati aren dan bentonit (Rahayu & Purnavita, 2014), arang aktif dari kulit salak (Mangallo, 2014), dan durian arang kulit (Masyithah et al, 2018). Berdasarkan penelitian yang dilakukan oleh Masyithah, dkk.…”
Section: Introductionunclassified